PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA MANIPULATIF SEKOLAH DASAR NEGERI 09 SINGKAWANG TENGAH - Ikhsan, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this study is "the low learning outcomes of students on learning mathematics in class V Elementary School 09 Singkawang. The purpose of this study is to determine whether the application of learning by using manipulative media on learning mathematics can improve student learning outcomes in class V Elementary School 09 Singkawang.. While this form of research is classroom action research (PTK) which is collaborative by following class action research procedure that is planning, implementation, observation and reflection. The subject of this research is the researcher and the students of class V Elementary School 09 Singkawang Tengah semester II academic year 2016/2017 which amounted to 26 students. The data collected in the form of data scores the ability of teachers to plan and implement the learning. Data in the form of score of student learning outcomes. Data collection techniques consist of direct observation and measurement techniques. Data collection tools are observation lakes and test instruments. The test consists of a written test. Data analysis using descriptive analysis with the calculation of the average and percentage. Implementation of this class action carried out 3 cycles. The research results are: the ability of researchers in planning the learning, the average score of cycle I of 2.95, increased in cycle II of 3.27 and increased in the third cycle of 3.84. The ability of researchers in implementing learning, the average score of cycle I of 2.80, increased in cycle II of 3.08 and increased in the third cycle of 3.63. The average value of students on learning calculate the volume of cubes and beams using the media manipulative cycle I 52.30 with learning completeness 26.92%, increased in cycle II 72.30 with learning completeness 57.69% and increased in cycle III 83.08 With learning mastery 84.62%. It was concluded that there was an increase in student learning outcomes in learning to calculate the volume of cubes and beams using manipulative media of unit cubes in class V Elementary School 09 Singkawang. Keywords: Improvement, learning outcomes, mathematics, manipulative media.